Pengujian Kinerja Sistem Pendeteksi Kebocoran Kompor Gas LPG Berbasis Internet of Things pada Kondisi Lingkungan yang Berbeda - Anggraini Mulwinda; Budi Sunarko; Riana Defi Mahadji Putri; Agus Suryanto; Dhea Puspitasari (Lembaga Pengembangan Kinerja Dosen, 2026)
Liquefied Petroleum Gas (LPG) serves as the primary cooking fuel in Indonesia, with around 88.59% of households relying on gas energy for their daily cooking tasks. The significant reliance on LPG raises the threat of gas leaks, which can cause fires and jeopardize the safety of users. Consequently, there is a need for a dependable early detection system that can deliver swift alerts and facilitate remote monitoring. This research aims to create and develop a gas leakage detection system utilizing Internet of Things (IoT) technology, incorporating an MQ-2 gas sensor and an ESP32 microcontroller. The methodology used in this study follows a Research and Development (R&D) approach, which includes stages of planning, production, and evaluation. The system features local alarms comprised of LEDs and a buzzer, alongside real-time monitoring and notification capabilities through the Blynk application. Experimental results show that the MQ-2 sensor is able to detect LPG gas concentrations in the range of approximately 410 PPM to over 2000 PPM. Performance evaluation indicates that the system responds faster and more consistently in a closed-space environment, with an average response time of ±3.8 seconds, compared to an open-space environment with an average response time of ±5.8 seconds. These findings demonstrate that environmental conditions significantly affect system performance, and the proposed system is effective as an early warning tool for LPG gas leakage in household environments.